EP497 Adjuvant/radical radiotherapy in elderly women with endometrial cancer: is it justified based on survival outcomes?. (1st November 2019) - Cunningham, C; Chitoni, M; Kerr, A; Harrand, R; Sadozye, A; Reed, N; Graham, K
Abstract : Introduction/Background: Endometrial cancer is largely a disease of older women. The incidence is increasing and age is a prognostic factor, with subsequent resource implications. Poorer outcomes may be due to biological factors and/or suboptimal treatment. Interestingly, PORTEC-3 indicates that high-risk women >70 years benefit from adjuvant chemoradiotherapy (5-year OS 67%). We investigated real-world outcomes of elderly women in West of Scotland Cancer Network (WoSCAN) who received pelvic external beam radiotherapy (PRT) for endometrial cancer. Methodology: Data were collected retrospectively from WoSCAN electronic clinical records in women 70 years who commenced PRT for endometrial cancer between January 2011 and December 2015. Statistical analysis was performed using R®. Overall survival (OS) was estimated using Kaplan-Meier method. Results: 93 patients were identified. The median age was 75 years (range 70–90); 28% >80years. Median number of co-morbidities was 2 (range 0–7). Treatment intent was as follows: adjuvant (60%), primary (inoperable) (21%), salvage (vault/pelvic recurrence) (19%). Only 30% had Stage 1 disease, over 25% had aggressive pathology. 90% completed all radiotherapy as planned (4500cGy/25# ± brachytherapy), 5% discontinued PRT and 5% completed PRT but defaulted from brachytherapy. 30-day mortality was 5%. Over 50% received chemotherapy. 5-year OS was 50%. Enhanced OS was associated with low-grade pathology, early stage and adjuvant/salvage intent; 5-year OS 55% (adjuvant/salvage) versus 20% (primary). OS was significantly worse in >80 cohort (25%) compared with 70–79 cohort (55%). Conclusion: Compliance with PRT for endometrial cancer in women >70 years is >90%. OS in adjuvant setting is slightly less favourable than PORTEC-3 but we included very elderly women, often with multiple medical co-morbidities. PRT is justified in patients aged 70–79 years. However, it may be appropriate to consider a more pragmatic approach in women >80 years, especially in the context of inoperable disease, as survival may not be sufficiently long to benefit from aggressive therapy. Disclosure: Nothing to disclose.